(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India being an underdeveloped country with a large population of employable educated youths, faces severe unemployment situation. The government of India as well as State Governments are consciously pursuing a policy of supporting of the industrial development and extending all possible assistance to the industrial sector. Keeping in view this situation it has introduced Start-Ups, Mudra loans, support to self-employment endeavour and the response is very positive